Better oral hygiene is associated with a reduced risk of osteoporotic fracture: a nationwide cohort study - Park, Jung-Hyun; Park, Moo-Seok; Kim, Hyung-Jun; Lee, Heajung; Kim, Jin-Woo; Song, Tae-Jin (Frontiers in Endocrinology, 2023)
Background: The aim of this study was to examine the longitudinal association between oral health parameters and osteoporotic fracture.Methods: The study included participants who received oral health screening by dentists from the National Health Screening cohort database of Korea between 2003 and 2006. The primary outcome was osteoporotic fracture occurrence, which was defined using specific international classification of diseases-10 codes; vertebral fracture (S22.0, S22.1, S32.0, S32.7, T08, M48.4, M48.5, and M49.5), hip fracture (S72.0 and S72.1), distal radius fracture (S52.5 and S52.6), and humerus fracture (S42.2 and S42.3). The presence of periodontitis and various oral health examination findings, such as missing teeth, caries, frequency of tooth brushing, and dental scaling, were analyzed using a Cox proportional hazard model to assess their association with osteoporotic fracture occurrence.Results: The analysis included a total of 194,192 participants, among whom 16,683 (8.59%) developed osteoporotic fracture during a median follow-up of 10.3 years. Poor oral health status, including periodontitis (adjusted hazard ratio [aHR]: 1.09, 95% confidence interval [